Growth Mindset Based Teacher Supervision Model In Education: Literature Review - Hakim, Athrusy Robiul; Setyawan, Jefri Nanang; Afriani, Linda; Mutmainnah; Bafadal, Ibrahim; Ubaidillah, Aan Fardani (Sekolah Tinggi Agama Islam Al-Muntahy, 2025)
The growth mindset-based teacher supervision model is an innovative approach in the development of teacher professionalism that emphasizes the mindset that abilities can continue to be developed through effort, perseverance, and self-reflection. This study aims to formulate a more humanistic and strategic model of supervision by focusing on the growth of teachers as lifelong learners. Through the literature review method, this study examines relevant theories and the results of previous studies that support the concept of growth mindset in education. This model is structured in a controlling cycle framework that includes five main stages: standardization, data-driven monitoring, deviation detection, corrective action, and feedback loop. Indicators of teacher mindset growth include active participation in professional development, learning innovation, acceptance of feedback, and self-reflection skills. In addition, this model is enriched with evaluation instruments such as reflective journals, peer review, and collaborative coaching. The results of the study show that the implementation of growth mindset-based supervision is able to create a school culture that is adaptive, collaborative, and oriented towards improving the quality of education. Thus, this model is expected to be a practical and theoretical reference for school principals and education supervisors in improving the quality of teacher human resources in a sustainable manner in the midst of today's educational challenges.